RESEARCH OF DEFLECTIONS OF THE UNDERCRANE BEAM DURING THE OPERATION OF A BRIDGE CRANE USING THE METHOD OF LASER INTERFEROMETRY - Hrytsenko, V. (Municipal economy of cities. Series: «Economy science», 2023)
Assessment of deformations and displacements of building structures is performed by solving many different problems. Depending on the specifics of the task, different measurement accuracy is required. In some displacement measurements, direct contact of the measuring device with some points of the structure under research is impossible: distant and high-placed structures, structures in the high temperature zone, etc. Contact with the measuring device of structures made of materials with low rigidity, thin films, elastic threads, or in cases where the material reaches the yield point is undesirable. In these cases, the inherent rigidity of the measuring device can distort the general picture of deformations, which will lead to significant errors. The article discusses modern methods of laser interferometry for non-contact assessment of movements and deformations of building structures, which make it possible to conduct unique non-contact measurements of both small and large deformations of various structures. The scientific value of the article lies in the fact that for the non-contact assessment of movements and deformations of building structures, it is proposed to use the most modern methods of laser interferometry, which make it possible to conduct unique non-contact measurements of both small and large deformations of various structures that work elastically, non-linearly, or are in plastic state in experimental conditions of high temperatures, radiation, with the provision of a high degree of automation of measurements and processing of results. The practical value of the research consists in the development of a technique that offers a non-contact assessment of movements and deformations of building structures using laser interferometry and makes it possible to provide measurements with an accuracy of 1×10-8 m and a frequency of 10-100 measurements per second with automation of registration and processing of results; carry out studies of building structures, buildings and structures in the mechanics of deformed solids and in the technique of surveying building structures, determining their performance, especially in conditions of high temperatures during fire resistance tests, in conditions of increased radiation, where high-precision and at the same time easy-to-use methods are required automated methods. The proposed technique provides unique opportunities for non-contact assessment of small deformations when studying the phenomena of shrinkage, swelling, creep, and plastic deformations.